Evaluación del uso de nanopartículas tipo látex en el fluido de perforación a nivel de laboratorio para el control de inestabilidad de pozos en la formación bambucá del Campo Venganza (2020)
In the drilling of a well, it is required that the formulation of the sludge be adequate to maintain stability, this parameter being a problem that has arisen in the drilling operations of the Venganza Field, due to the presence of formations with high content of lutites, subjected by high concentration of characteristic efforts in the basin of the Upper Valley of the Magdalena , or physicochemical interactions between the drilling fluid and the formation, or a combination of both. Initially 4 correlation wells were selected, in which problems of instability were identified in both water-based and oil-based fluids, between 2000 and 2012, whose instability was present in the Bambucá formation, belonging to the Villeta group, where there is evidence of accumulation of abundant caving, pipe glues and restrictions in pipe travel operations, these problems were associated with the directional plan performed and the drilling fluid used in that section.